THE SYNDROME OF UNFORTUNATE CONSEQUENCES HELPPA (Modern education and development, 2024)
HELLP syndrome includes hemolysis (H-hemoIisis), increased activity of liver enzymes (el - elevated liver enzymes) and a decrease in platelet count (Ip - low playlet count), usually manifests itself as a complication of preeclampsia, but can also develop independently. HELLP syndrome develops with a frequency of 1-6 cases per 1000 pregnancies and in 4-12% of patients with severe preeclampsia. Preeclampsia is characterized hypertension, proteinuria and edema in the second or third trimester of pregnancy and develops in 5-7% of pregnant women. In 70% of cases, HELLP syndrome develops before childbirth, in 30% - in the postpartum period.